2011
DOI: 10.1177/009318531103900208
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Job Satisfaction in Massachusetts Judges

Abstract: This pilot study examined the overall job satisfaction of Massachusetts judges, and additionally addressed these judges' views of what might serve to increase their job satisfaction. Results indicated that these judges were highly satisfied with their jobs, and that they viewed increased pay as the most important contributor to increased job satisfaction, followed by improvements in professional support staff. Various other factors, including geographic location and the availability of computer networking, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Nine out of 10 (92%) judicial officers were satisfied, including very satisfied, with their work (88% women and 94% men). The pilot study of Norris et al (2011) regarding job satisfaction of judges in Massachusetts displayed similar results. They found that, on a scale of 1 ('dissatisfied') to 6 ('completely satisfied'), the lion's share of the sample appraised their satisfaction as 5 or 6.…”
Section: Job Satisfactionmentioning
confidence: 58%
See 1 more Smart Citation
“…Nine out of 10 (92%) judicial officers were satisfied, including very satisfied, with their work (88% women and 94% men). The pilot study of Norris et al (2011) regarding job satisfaction of judges in Massachusetts displayed similar results. They found that, on a scale of 1 ('dissatisfied') to 6 ('completely satisfied'), the lion's share of the sample appraised their satisfaction as 5 or 6.…”
Section: Job Satisfactionmentioning
confidence: 58%
“…They were interviewed between 4 and 8 weeks after the shooting. 8 Norris, Commons, Miller, Adams and Gutheil (2011) United States A pilot study relating to judges in Massachusetts was conducted to establish the extent of their perceived satisfaction in an objective, empirical way, via a Rasch analysis. Anonymous surveys.…”
Section: Ethical Considerationmentioning
confidence: 99%
“…Job resources, therefore, can potentially encourage individuals' personal development and learning and help them to attain their objectives (Demerouti & Bakker, 2011;Schaufeli & Bakker, 2004). Studies in other countries found that judges' job resources include, amongst others, autonomy and positive co-worker relations (Ludewig & Lallave, 2013;Norris, Commons, Miller, Adams, & Gutheil, 2011).…”
Section: Judges' Job Demands and Job Resourcesmentioning
confidence: 99%
“…More importantly, job satisfaction (or dissatisfaction) can pinpoint gender and other inequalities or discrimination in occupations (Dinovitzer and Garth, 2007;Hull, 1999). Studies of gender and job satisfaction have not considered the judiciary (Dinovitzer and Garth, 2007) and discussions of job satisfaction among judges have not tended to examine gender (Chase and Hora, 2009;Darbyshire, 2011;Norris et al, 2011;Ryan et al, 1980; for an exception, see Roach Anleu and Mack, 2009). Studies of gender and job satisfaction have not considered the judiciary (Dinovitzer and Garth, 2007) and discussions of job satisfaction among judges have not tended to examine gender (Chase and Hora, 2009;Darbyshire, 2011;Norris et al, 2011;Ryan et al, 1980; for an exception, see Roach Anleu and Mack, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such disparities can be masked by the apparent gender equality shown by increasing proportions of women entering higher level, traditionally male professions such as the judiciary. Studies of gender and job satisfaction have not considered the judiciary (Dinovitzer and Garth, 2007) and discussions of job satisfaction among judges have not tended to examine gender (Chase and Hora, 2009;Darbyshire, 2011;Norris et al, 2011;Ryan et al, 1980; for an exception, see Roach Anleu and Mack, 2009). This article fills that gap.…”
Section: Introductionmentioning
confidence: 99%